Assessment of the Impact of Coronavirus (Covid-19) Pandemic on Educational System in Nigeria: Implication for Stakeholders - Suleiman, Yusuf; Adam Ishola, Mustapha (UMT Education Review, 2020)
The spread of coronavirus pandemic (COVID-19) is a trending issue that has become a global threat to the development of all countries in the world. The disease has affected all sectors of the economy, including sports, education, etcetera. This study examined the impactof the Corona Virus on the educational system in Nigeria and its implication for stakeholders. The spread of the pandemic was analyzed using the reports emanated from reliable sources. The pandemic’s effects include the closure of schools at all levels, delay in completion of an academic degree, risky decision making, rise in public and private partnership, online teaching, and students’ learning outcomes. The implication for stakeholders includes the government’s need to provide an up-to-date report on the pandemic’s spread to protect institutions’ inhabitants. School authorities should provide teaching through online platforms (Zoom, Skype, Whatsapp, Googlemate, Email, etcetera). There should be synergy between school management and parents to ensure that students receive the teaching provided online. Also, parents should assist their children by providing them the necessary gadgets needed for learning online. Moreover, the students should be taught precautionary measures that will enable them to stay safe for the post-coronavirus era.